Measuring empowerment in practice : structuring analysis and framing indicators - Alsop, Ruth.; Heinsohn, Nina.; World Bank. Poverty Reduction and Economic Management. Poverty Reduction Group (Washington, D.C. : World Bank, Poverty Reduction and Economic Management Network, Poverty Reduction Group, 2005)
"Alsop and Heinsohn present an analytic framework that can be used to measure and monitor empowerment processes and outcomes. The measuring empowerment framework, rooted in both conceptual discourse and measurement practice, illustrates how to gather data on empowerment and structure its analysis. The framework can be used to measure empowerment at both the intervention level and the country level, as a part of poverty or governance monitoring. The authors first provide a definition of empowerment and then explain how the concept can be reduced to measurable components. Empowerment is defined as a person's capacity to make effective choices--that is, the capacity to transform choices into desired actions and outcomes." -- Cover verso.
"February 2005" -- Cover.
Includes bibliographical references (p. 32-34).
Also available on the Internet.
Keywords: Decision making; Employee empowerment